Novel Organoselenium Redox Modulators with Potential Anticancer, Antimicrobial, and Antioxidant Activities - Marwa Sak; Yasair S. Al-Faiyz; Hany Elsawy; Saad Shaaban (MDPI AG, 2022)
Novel organic selenides were developed in good yields (up to 91%), and their chemical entities were confirmed by IR, MS, and 1H- and 13C-NMR spectroscopy. Their anticancer and antimicrobial properties were estimated against different human cancer (MCF-7 and HepG2) and healthy (WI-38) cell lines, as well as several microbial strains (Escherichia coli, Staphylococcus aureus, and Candida albicans). Furthermore, the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) bioassays were used for the estimation of the antioxidant activities. Generally, cytotoxicity results were more pronounced against the MCF-7 cells than HepG2 cells. Compound 2-((4-((1-hydroxynaphthalen-2-yl)diazenyl)phenyl)selanyl)-N-phenylacetamide (9) was the most cytotoxic, even more than doxorubicin, with IC50 of 3.27 ± 0.2 against 4.17 ± 0.2 µM and twelve-times more selective, respectively. Interestingly, compound 9 exhibited similar antimicrobial potential to reference antibacterial and antifungal drugs and comparable antioxidant activity to vitamin C. These results point to selective cytotoxicity against MCF-7 cells and interesting antimicrobial and antioxidant properties of some newly synthesized organic selenides, which in turn needs further in vitro studies.